2021
DOI: 10.5194/acp-21-16219-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Spatiotemporal and policy-related variations of PM<sub>2.5</sub> composition and sources during 2015–2019 at multiple sites in a Chinese megacity

Abstract: Abstract. A thorough understanding of the relationship between urbanization and PM2.5 (fine particulate matter with aerodynamic diameter less than 2.5 µm) variation is crucial for researchers and policymakers to study health effects and improve air quality. In this study, we selected a rapidly developing Chinese megacity, Chengdu, as the study area to investigate the spatiotemporal and policy-related variations of PM2.5 composition and sources based on long-term observation at multiple sites. A total of 836 sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…The decreasing rates of deweathered NO 2 (17.3%) and SO 2 (30.0%) during 2013–2017 were slightly higher or comparable to those during 2018–2021 (9.08% and 29.0%) in BTH, while they displayed opposite characteristics in YRD and PRD. Such characteristic confirmed that emission reduction measures in YRD and PRD have been further strengthened after 2018 (Feng et al., 2021; Yang et al., 2022) and the emission control measures in these regions might be more efficient than BTH. In fact, BTH still suffered from severe NO 2 pollution compared with other regions in China, and thus it is urgent to further decrease NO 2 level in this region.…”
Section: Resultssupporting
confidence: 55%
“…The decreasing rates of deweathered NO 2 (17.3%) and SO 2 (30.0%) during 2013–2017 were slightly higher or comparable to those during 2018–2021 (9.08% and 29.0%) in BTH, while they displayed opposite characteristics in YRD and PRD. Such characteristic confirmed that emission reduction measures in YRD and PRD have been further strengthened after 2018 (Feng et al., 2021; Yang et al., 2022) and the emission control measures in these regions might be more efficient than BTH. In fact, BTH still suffered from severe NO 2 pollution compared with other regions in China, and thus it is urgent to further decrease NO 2 level in this region.…”
Section: Resultssupporting
confidence: 55%
“…The result suggests that the contribution of chemical composition related to secondary formation has increased in recent years. However, the proportion of MD was still substantially higher than those of other cities in South China (Huang et al, 2013a); southwest China (Feng et al, 2021); southeast China (Li et al, 2017b); and the Central Plains Urban Agglomeration (Liu et al, 2019), which is close to the cities in northern China (Liu et al, 2021;Xie et al, 2019) and northwest China (Zhou et al, 2021). The lower RH, higher WS and larger area of uncovered surface soil lead to frequent dust storms in semi-arid regions, resulting in a higher contribution of MD than in the humid area (Liang et al, 2019).…”
Section: Temporal Variation In Pmmentioning
confidence: 91%
“…CC BY 4.0 License. (Feng et al, 2021). In this study, the meteorological data used for the HYSPLIT model and the CWT method remained the same.…”
Section: Source Apportionment By Backward Trajectory Calculation and ...mentioning
confidence: 99%